Marinagarivorans cellulosilyticus sp. nov., a cellulolytic bacterium isolated from the deep-sea off Noma-misaki, Japan. Issue 3 (2nd March 2023) - Tsudome, Mikiko; Tachioka, Mikako; Miyazaki, Masayuki; Tsuda, Miwako; Takaki, Yoshihiro; Deguchi, Shigeru
Abstract : Cells from strain GE09 T, isolated from an artificially immersed nanofibrous cellulose plate in the deep sea, were Gram-stain-negative, motile, aerobic cells that could grow with cellulose as their only nutrient. Strain GE09 T was placed among members of Cellvibrionaceae, in the Gammaproteobacteria, with Marinagarivorans algicola Z1 T, a marine degrader of agar, as the closest relative (97.4 % similarity). The average nucleotide identity and digital DNA–DNA hybridization values between GE09 T and M. algicola Z1 T were 72.5 and 21.2 %, respectively. Strain GE09 T degraded cellulose, xylan and pectin, but not starch, chitin and agar. The different carbohydrate-active enzymes encoded in the genomes of strain GE09 T and M. algicola Z1 T highlights their differences in terms of target energy sources and reflects their isolation environments. The major cellular fatty acids of strain GE09 T were C18 : 1  ω 7 c, C16 : 0 and C16 : 1  ω 7 c . The polar lipid profile showed phosphatidylglycerol and phosphatidylethanolamine. The major respiratory quinone was Q-8. Based on these distinct taxonomic characteristics, strain GE09 T represents a new species in the genus Marinagarivorans, for which we propose the name Marinagarivorans cellulosilyticus sp. nov. (type strain GE09 T =DSM 113420 T =JCM 35003 T ).